Consumers and consumption in comparison - Dulsrud, Arne (Comparative social research, 2024)
Consumption studies are underrated in the social sciences. Drawing specific attention to this need for further analysis, this latest volume of Comparative Social Research presents a rich collection of chapters offering an up-to-date view of the sociology of consumption. Providing a theoretically informed discussion of the specificities of sociology of consumption, Consumers and Consumption in Comparison focuses on three main approaches: Consumption and social inequality; Consumption and gender; and Consumption and social movements. With chapters covering consumer collective action, health and food consumption, sustainable consumption, the cost-of-living crises, gendered online play, and more, this is compelling read for scholars across the social sciences interested in a comparative view of consumers and consumptions.